KEMAMPUAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP MUHAMMADIYAH 1 PEKANBARU - Astuti, Afrilia; Elmustian, Elmustian; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study examines the ability to write the persuasion text of the students of grade VIII SMP Muhammadiyah 1 Pekanbaru. The purpose of this study is to describe how high the level of writing skills of persuasion text of students of class VIII SMP Muhammadiyah 1 and describe the differences in the ability to write explanatory text between groups or between classes. This study has a population of 126 and a sample of 96. The results when tested using the Wilcoxon Test is the ability to write persuasion text equal to the value of comparison. The comparative value applied in this study was 82. The students writing ability was the same as the comparison score, which means that the ability to write high school students persuasion text is high. In other words the hypothesis is accepted. Then tested by using Kruskall Wallis. The result is that there is no difference in the ability of writing explanatory text of class VIII students between classes. Based on the results of research writers can be seen that the ability to write students are high because students have complete facilities and teachers are very creative in teaching and learning process. In addition, teachers who teach at the school are young and have high spirits. Although the school is private, but has accreditation A.Keywords: Ability, Writing, Persuasion Text, Student